Integrasi Nilai-Nilai Profil Pelajar Pancasila dalam Pembelajaran PAI (Studi Kasus di SMAN 2 Tanjung) - Muhammad Ichsan Rahmadani; Umiarso; Mohammad Kamaludin (LPPM STAI Al-Azhar Menganti Gresik, 2023)
Pancasila Student Profile as the basis for Independent Curriculum contains significant values in the development of excellent human resources. The aspect of independence in this curriculum does not mean the absent of responsibility in facilitating students, but instead a requirement for the learning activities to not limit the potential of students. The implementation of this latest curriculum requires a comprehensive integration of the values of the Pancasila Student Profile, which in this case is specified to Pendidikan Agama Islam (PAI). This study aims to identify the process of integrating the values of the Pancasila Student Profile in PAI at SMAN 2 Tanjung. Researchers used a qualitative approach through case study method and data analysis through descriptive analysis methods. The results showed that the integration of the values of the Pancasila Student Profile in PAI at SMAN 2 Tanjung has been well performed using the Webbed model by Fogarty, where the Pancasila Student Profile is the core theme in the learning. But the effectiveness of learning activities can be further improved by using more variation in methods and media of learning, so that students will be more enthusiastic on participating in learning at the class.